2012
DOI: 10.3151/jact.10.313
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Protective Performance of Cracked Ultra High Performance-Strain Hardening Cementitious Composites (UHP-SHCC) Due to Autogenous Healing

Abstract: A new strain hardening cementitious composite with a dense matrix, Ultra High Performance-Strain Hardening Cementitious Composites (UHP-SHCC), has been developed. This material combines excellent protective performance with a significantly higher tensile strength and strain hardening at tensile strength. Further, the material has controlled fine cracks (less than 30 microns). A low water to binder ratio with silica fume that causes a pozzolanic reaction is used in UHP-SHCC. These characteristic may give advant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…Although in a few cases it was observed that the specimens cured in air could be healed if the healing period was sufficiently long, the water condition was better for the self-healing of concrete. The healing tendency according to the healing condition is consistent with the results of many other studies [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][36][37]41,43]. It is a reasonable The results of the flexural strength comparison and the initial flexural stiffness comparison are similar if we look at the results themselves.…”
Section: Self-healing Assessment Based On Initial Flexural Stiffnesssupporting
confidence: 88%
See 1 more Smart Citation
“…Although in a few cases it was observed that the specimens cured in air could be healed if the healing period was sufficiently long, the water condition was better for the self-healing of concrete. The healing tendency according to the healing condition is consistent with the results of many other studies [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][36][37]41,43]. It is a reasonable The results of the flexural strength comparison and the initial flexural stiffness comparison are similar if we look at the results themselves.…”
Section: Self-healing Assessment Based On Initial Flexural Stiffnesssupporting
confidence: 88%
“…Another famous active method was proposed based on the use of microorganisms [21][22][23][24], which help deposit crack-restoring substances. Moreover, many passive methods exist, for example, improvement of self-healing environment using fibers that prevent the occurrence of a single large crack and induce multiple cracks of small width [25][26][27][28]. The recovery due to self-healing is not only general strength recovery but also durability recovery such as decreased water permeability [29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…After this time, its flexural tensile strength was approximately 30% higher than that of the reference material that was stored in air-dry conditions. Also, the research conducted by (Kunieda et al 2012) unambiguously confirms the ability of UHPC to selfheal its structure. Investigations of this phenomenon conducted by the authors were based, inter alia, on the characteristics of the composites ability to transport liquid and gas media.…”
Section: Introductionmentioning
confidence: 62%
“…Fine cracks were observed as healed using hybrid fibers. Kunieda et al [132] used a high strength matrix and 88 GPa high-stiffness PE fibers to produce PE-ECC, which exhibited a good self-healing effect. The crack width in the research was less than that of normal ECC due to the strong restriction by PE fibers.…”
Section: The Self-healing Effect Of Cementitious Composites With Pe Fibersmentioning
confidence: 99%